AN OVERVIEW OF PHOTOVOLTAIC CELLS: THEIR WORKING PRINCIPLES, MATERIALS, FABRICATION METHODS, CHALLENGES AND REMEDIES (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
One of the primary causes of climate variability is the frequent use of non-renewable energy resources, highlighting the imperative need for sustainable substitutes. At the vanguard of this shift are photovoltaic (PV) cells, semiconductor components that directly transform solar energy into electricity. This paper offers an overview of PV cells, highlighting their working principles, materials, fabrication techniques, current technological status, research and development (R&D) trends, and challenges with recommended remedies. Emphasis is on crystalline silicon (c-Si), thin-film technologies, perovskite solar cells (PSCs) and hybrid tandem configurations. Although some challenges still exist, recent developments have greatly increased efficiency and lowered costs. These consist of integration into current grids, operational instability, environmental issues, and high material expenses. Amongst other research remedies are the development of lead-free perovskites, improved passivation techniques, nanostructuring, recycling methods, and circular economy policies. Supported by International partnerships and policy incentives, ongoing research and development (R&D) projects, seek to move laboratory-scale innovations to commercially viable solutions. This article, therefore, highlights the necessity of continuous innovation to utilize solar energy as a main driver of the global energy balance.